2010
DOI: 10.1139/o10-012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant polyphenols on ovarian follicular reserve in aging ratsThis paper is one of a selection of papers published in this special issue entitled “Second International Symposium on Recent Advances in Basic, Clinical, and Social Medicine” and has undergone the Journal's usual peer review process.

Abstract: The pool of ovarian primordial follicles is established during embryonic development or at birth. During the development from primordial to primary, secondary, and antral follicles, only a small portion of follicles can mature and successfully ovulate; the others are destined to degenerate through apoptotic or atretic loss. As aging advances, females ultimately enter the cessation phase of the estrous cycle and are no longer capable of fertilization. The presumption is that if we can slow down the process of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…In support of these data, a similar study showed that pretreatment of irradiated rats with RVT at different doses significantly protected the ovarian follicle counts and markedly increased the AOX enzymes (Simsek et al, 2012). RVT effectively protected the ovarian follicular reserve by inhibiting follicular atresia in aging rats (Chen et al, 2010). In contrast RVT displayed an apoptotic effect on theca interstitial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In support of these data, a similar study showed that pretreatment of irradiated rats with RVT at different doses significantly protected the ovarian follicle counts and markedly increased the AOX enzymes (Simsek et al, 2012). RVT effectively protected the ovarian follicular reserve by inhibiting follicular atresia in aging rats (Chen et al, 2010). In contrast RVT displayed an apoptotic effect on theca interstitial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants play a protective role against oxidative damage caused by thermal stress in the cells and tissues of organisms. The positive effects of antioxidants have been reported regarding several reproductive aspects [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ] and the recovery of injuries induced by thermal stresses [ 49 , 50 ]. Melatonin treatment for high-yielding dairy cows during a dry period under thermal stress improved their reproductive performance and reduced the rates of breeding syndrome and pregnancy loss [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has anti-aging effect and also beneficial effects of cardiovascular and metabolic system [ 19 , 20 ]. Consistently, it prolongs the ovarian lifespan and protects against age-associated infertility in rodents [ 21 , 22 ]. However, resveratrol is not a specific activator of SIRT1, and it can also activate other signaling pathways [ 23 ].…”
Section: Introductionmentioning
confidence: 99%